Nonsurgical treatments in periodontics - Z. Kadkhoda; E. Baygan (Tehran University of Medical Sciences, 1995)
Both surgical and nonsurgical treatments are definitely effective in ameliorating periodontal condition. In nonsurgical treatments, pocket elimination is not an essential part but subgingival infection control is the main objective which can eliminate inflammation, stop destruction, form new attachments, decrease pocket depth (following edema decrease) and finally result in long junctional epithelium formation. In short term, surgery can eliminate pocket depth more effectively although after a while this difference would become less. Besides, nowadays according to infectious nature of periodontal diseases systemic and local antimicrobials are used along with nonsurgical and mechanical treatments specially in rapidly progressing periodontitis, HIV related periodontitis and refractory periodontitis . Therefore, the most appropriate and simplest treatment plan should be selected according to the type of periodontal disease.